2024
DOI: 10.1039/d3nr04305c
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular self-aggregation of biomimetic Fe3O4 nanoparticles for enhanced ferroptosis-inducing therapy of breast cancer

Zhendong Zhang,
Beibei Xie,
Xiaojie Lu
et al.

Abstract: A supramolecular and cell membrane co-modified drug delivery system was constructed to enhance Fe3O4 and SAS synergistically induced ferroptosis anti-tumor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Studies have shown that in the treatment of human fibrosarcoma, SAS can inhibit the expression of system Xc on the fibrosarcoma cell membrane, suggesting that SAS can inhibit the occurrence and development of tumors to a certain extent. The possible mechanism by which SAS induces ferroptosis is by interrupting the cystine uptake signaling pathway [29][30][31][32][33][34][35][36][37][38] . System Xc¯ is one of the key signal pathways of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in the treatment of human fibrosarcoma, SAS can inhibit the expression of system Xc on the fibrosarcoma cell membrane, suggesting that SAS can inhibit the occurrence and development of tumors to a certain extent. The possible mechanism by which SAS induces ferroptosis is by interrupting the cystine uptake signaling pathway [29][30][31][32][33][34][35][36][37][38] . System Xc¯ is one of the key signal pathways of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have created self-aggregating Fe 3 O 4 nanomaterials within tumor cells, prolonging the residence time to enhance ROS production and achieve a better ferroptosis therapy effect. [13] The scarcity of Fe 3 O 4 nanomaterials reported in the literature to enhance tumor cell ferroptosis efficacy necessitates the development of new strategies for Fe 3 O 4 nanomaterials to achieve a higher degree of ferroptosis therapy enhancement, combining it with immunotherapy for more efficient tumor growth suppression.…”
Section: Introductionmentioning
confidence: 99%